CHARACTERISTICS AND TRENDS OF THE DEVELOPMENT OF PILGRIMAGE TOURISM IN THE CONTEXT OF GLOBAL ECONOMIC CHANGES (Conferencea, 2023)
In the process of globalization of today's world economy, the international tourism industry is gaining importance as a source of high income. The impact of tourism on the socio-economic life of the country is manifested in foreign exchange earnings, creation of new jobs, development of small business and private entrepreneurship, mutual respect, tolerance, culture and values between peoples, nationalities and religions.